Development of a pneumatic centrifugal concentrator for the dry processing of ultrafine particles of auriferous minerals: design of the prototype - Mamani-Quispe, Jhon Marcelo (2022)
The objective of this work is the design of a prototype of a pneumatic centrifugal concentrator that allows small-scale mining that takes place in desert and isolated places, to process ultrafine gold minerals in situ, cleanly, without the use of water and chemical reagents. A mathematical model based on the physico-phenomenological analysis of the differential sedimentation separation mechanism was applied in a film of laminar flow fluid, to determine the particle trajectory inside the bowl of the centrifugal concentrator as a function of the variables of bowl geometry, operating variables and physical characteristics of the particle and fluid. The simulations carried out showed a remarkable effect of the use of air instead of water on the trajectory of the particles within the fluid film. The results also showed that the capacity of the concentrator for the separation of particles by density difference rather than by size difference, was favored when applying low rotation speeds, high air feed rates and for particle sizes in the ultrafine range (< 40 μm). The prototype built will allow to carry out experimental laboratory tests that complement the understanding of the process and refine the design of the concentrator.